PSVIII-25 Transcriptional reprogramming in rumen epithelium during the developmental transition of pre-ruminant to the ruminant in cattle. (8th October 2021) - Baldwin, Ransom L; Connor, Erin E; Ramsay, Timothy G; Liu, George E; Li, Cong-Jun
Abstract: The rumen is a critical organ mediating nutrient uptake and use in cattle. Healthy rumen development is essential to ensure animal feed efficiency. In this work, we present an analysis of transcriptomic dynamics in rumen epithelium during the transition from pre-rumination to rumination in cattle-fed hay or concentrated diets at weaning (eighteen Holstein bull calves, 3 X 6 groups). These two distinct phases of rumen development and function in cattle are tightly regulated by a series of signaling events and clusters of effectors on key pathways. Our analysis identifies putative signaling events and effectors. Gene activity shifts indicated the transcriptomic reprogramming required to induce developmental changes in ruminal epithelium and functional transitions. A principal component analysis distinguished the temporal expression patterns that clustered separately between pre- and post-weaning groups. A GO-term enrichment analysis reflected functional (physical and metabolic) development of ruminal epithelium and revealed the greatest number of DEGs were enriched in biological processes related to energy metabolism. Canonical pathway and upstream regulator analyses revealed transcription reprogramming with clusters of critical pathways and upstream regulators controlling functional and developmental transitions with no significant differences between hay- and concentrate-fed groups at weaning. The most highly activated transcription factors expressed during the weaning transition were PPARGC1A, INSR, NFE2L2, MYC, MYCN, and PPARA. Overall, the dietary shift from liquid to solid feeds prompted transcriptional reprogramming in rumen epithelial tissue reflecting critical nutrient-gene interactions occurring during the developmental progression of ruminant digestion.